Three enactments of drugs in Danish prison drug treatment: Illegal drugs, medicine and constrainers - Kolind, T.; Holm, K.; Duff, Cameron; Frank, V. (Informa Healthcare, 2015)
© 2015 Taylor & Francis. Drugs are an increasingly salient concern in many European prisons. Drug policies are made, drugs are controlled, used and prescribed and drug use is treated and sanctioned. In light of the growing significance of drugs in prison life, we analyse the different ways of drugs that are enacted in Danish drug treatment programmes, based on insights derived from Science and Technology Studies. We ground our analysis with data from two qualitative research projects conducted between 2007 and 2010 and between 2011 and 2014. In all, eight prisons were involved in the two studies. Our analysis reveals three distinctive drug enactments characterised by rather different practises, discourses and narratives: drugs as illegal substances, as medicine and as constrainers. Furthermore, we examine how policy makers, prison officers, health personnel, counsellors and prisoners contribute to the construction and organisation of these three enactments, along with the practical and discursive domains in which this work takes place. We conclude by assessing some of the implications of these different enactments of drugs for prisoners’ subjectivities.